2021
DOI: 10.1016/j.esmoop.2021.100144
|View full text |Cite
|
Sign up to set email alerts
|

The role of homologous recombination deficiency testing in ovarian cancer and its clinical implications: do we need it?

Abstract: The recognition of homologous recombination deficiency (HRD) as a frequent feature of high-grade serous ovarian cancer (HGSOC) has transformed treatment paradigms. Poly(ADP-ribose) polymerase inhibitors (PARPis), developed based on the rationale of synthetic lethality that predicates antitumor efficacy in tumors harboring underlying HRD, now represents an important class of therapy for HGSOC. Recent data have drawn attention to the assessment of homologous recombination DNA repair (HRR) as a prognostic and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(101 citation statements)
references
References 80 publications
2
76
0
1
Order By: Relevance
“…High-grade serous ovarian cancer (HGSOC) is the most common type of EOC, accounting for 75% of all EOC, 15-20% of which western patients have germline BRCA1 or BRCA2 mutations. The BRCA mutation rate observed in our cohort was 35.8%, which was near the higher boundary of the previously reported range of 5 to 35% (14,22). Similar to other studies, we also observed BRCA1 mutations occurring more frequently than BRCA2 mutations in Chinese ovarian cancer patients (23,24).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…High-grade serous ovarian cancer (HGSOC) is the most common type of EOC, accounting for 75% of all EOC, 15-20% of which western patients have germline BRCA1 or BRCA2 mutations. The BRCA mutation rate observed in our cohort was 35.8%, which was near the higher boundary of the previously reported range of 5 to 35% (14,22). Similar to other studies, we also observed BRCA1 mutations occurring more frequently than BRCA2 mutations in Chinese ovarian cancer patients (23,24).…”
Section: Discussionsupporting
confidence: 89%
“…FoundationFocus ® CDx mainly evaluates HRD by loss of heterozygosity (LOH) with 16% as the threshold value that has been used for companion diagnostic (CDx) of rucaparib (11), while Myriad myChoice ® CDx includes LOH, telomere allele imbalance (TAI), and large fragment migration (LST) with 42 as the threshold value that has been widely applied for CDx of niraparib and olaparib (4,6,10,12). Approximately 50% of patients with high-grade serous ovarian cancer are HRD positive in the western population (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are five commercially available FDA-approved CDx tests for evaluating PARPi eligibility: BRACAnalysis CDx and MyChoice CDx from Myriad Genetic Laboratories, Inc., as well as FoundationOne CDx, FoundationFocus CDxBRCA, and FoundationOne Liquid CDx from Foundation Medicine ( 60 , 61 ). NGS-based CDx tests follow similar workflows: DNA is extracted from tissues and sequenced through NGS platforms, and then raw reads are processed through proprietary bioinformatics pipelines for variants calling and medical interpretation.…”
Section: Dna Damage Repair Pathways and Cancermentioning
confidence: 99%
“…The five CDx mentioned can all detect pathogenic or likely pathogenic variants of BRCA1/2. Among them, MyChoice CDx and FoundationOne CDx assays are prospectively validated assays for evaluation of HR deficiency status ( 61 ). The HR deficiency status can be assessed by checking the percentage of genomic regions with loss of heterozygosity (LOH) using single nucleotide polymorphism (SNP) sequencing or by calculation of the Genomic Instability Score (GIS) via coalescing three parameters: LOH, large scale transitions (LSTs) and telomeric allelic imbalance (TAI).…”
Section: Dna Damage Repair Pathways and Cancermentioning
confidence: 99%
“…Mainly used as indirect measures are the LOH determined by SNP-Sequencing, telomeric allelic imbalance (TAI), and large-scale state transitions (LST) for which each HRD score has been developed (143)(144)(145). Currently, for clinical routine use, only two prospectively validated and commercially available tests for assessment of HRD status are available (146): the myChoice CDx (Myriad Genetics) calculates a score based on all three genomic instability features and also includes BRCA1/2 mutations. In contrast, the FoundationOne CDx (Foundation Medicine) only calculates the percentage of genomic LOH.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%